Córki Syjońskie (Iz 3, 16-24) - Anna Rambiert-Kwaśniewska (Wrocławski Przegląd Teologiczny)
Passus from Iz 3,16-24 describing splendor of Zion’s daughters is without a doubt a perfect base to perform a comparison between the Hebrew Bible and Septuagint. It is hard to identify many of the Hebrew hapax legomena used by Isaiah, however, this is not this particular difficulty that can be seen as a cause of differences in translation of LXX. Thorough analysis shows, that Greek translator made an acculturation of the text to Egyptian conditions, as the list of goods he compiles has its representation in papyrus texts, in particular in these listing items in bride’s dowry. Explanation based on the culture is, however, not sufficient, since Greek version of the fragment can be also interpreted by using specifically “vailed” theology. This is because the translator adds to his version of text the same precious items, which has been used, according to LXX Ex to build the tabernacle at the desert. It is well seen in analogies between LXXIsa 3,20 and LXXEx 35,22, and also LXXIsa 3,23 and LXXEx 25,4. In this context explaining the difference between LXX and Hebrew Bible by referring to different Vorlage cannot be justified and proved.